2016
DOI: 10.1007/s10157-016-1281-9
|View full text |Cite
|
Sign up to set email alerts
|

Increased non-HDL-C level linked with a rapid rate of renal function decline in HIV-infected patients

Abstract: Increased non-HDL-C levels are a risk factor for renal function decline in HIV-infected patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 43 publications
1
6
0
4
Order By: Relevance
“…Chronically low HDL levels are associated with progression of CKD in patients with HIV and patients with type 2 diabetes . Similar results were demonstrated in two epidemiological studies that evaluated the risk factors for the development of kidney disease.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Chronically low HDL levels are associated with progression of CKD in patients with HIV and patients with type 2 diabetes . Similar results were demonstrated in two epidemiological studies that evaluated the risk factors for the development of kidney disease.…”
Section: Discussionsupporting
confidence: 78%
“…Prior studies postulated that the mechanism through which low HDL levels were associated with decreased renal function was through the coexistent high levels of non‐HDL cholesterol . Increased non‐HDL cholesterol may facilitate intra‐renal arteriosclerosis , microalbuminuria and lipid‐induced glomerular toxicity , precipitating renal dysfunction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that the prevalence of chronic kidney disease in HIV-positive patients in Japan is 15.4% [7]. Hara et al reported that chronic kidney disease in HIV-positive patients progresses more rapidly than that in non-HIV patients [8]. Rasch et al reported that the introduction rate of hemodialysis in HIV positive patients is 3.6 times higher than that of non-HIV patients [9].…”
Section: Discussionmentioning
confidence: 99%
“…A rapid annual reduction in eGFR in HIV-infected patients Kooij et al showed that being HIV-infected was independently associated with greater eGFR decline (− 1.59 [95% CI, − 0.87 to − 0.24] mL/min/1.73 m 2 /year in HIVinfected patients vs. − 0.69 [95% CI, − 0.91 to − 0.48] mL/min/1.73 m 2 /year in HIV-uninfected individuals; P = 0.001) among 479 HIV-infected and 377 HIV-uninfected individuals (median follow-up 3.9 and 4.1 years, respectively) [35]. In Japan, Hara et al longitudinally studied the rate of change in eGFR in 509 HIV-infected patients (598 males and 63 females, mean age 46.4 years) [36]. During the 6 years from 2008 to 2014, eGFR decreased at a mean annual rate of 2.01 mL/min/1.73 m 2 .…”
Section: Characteristics Of Ckd In Hiv-infected Patients In Japanmentioning
confidence: 99%